Drosophila Atlastin regulates synaptic vesicle mobilization independent of bone morphogenetic protein signaling - Francisca Bertin; Jorge Jara-Wilde; Benedikt Auer; Andrés Köhler-Solís; Carolina González-Silva; Ulrich Thomas; Jimena Sierralta (Biological Research, 2023)
Abstract Background The endoplasmic reticulum (ER) contacts endosomes in all parts of a motor neuron, including the axon and presynaptic terminal, to move structural proteins, proteins that send signals, and lipids over long distances. Atlastin (Atl), a large GTPase, is required for membrane fusion and the structural dynamics of the ER tubules. Atl mutations are the second most common cause of Hereditary Spastic Paraplegia (HSP), which causes spasticity in both sexes’ lower extremities. Through an unknown mechanism, Atl mutations stimulate the BMP (bone morphogenetic protein) pathway in vertebrates and Drosophila. Synaptic defects are caused by atl mutations, which affect the abundance and distribution of synaptic vesicles (SV) in the bouton. We hypothesize that BMP signaling, does not cause Atl-dependent SV abnormalities in Drosophila. Results We show that atl knockdown in motor neurons (Atl-KD) increases synaptic and satellite boutons in the same way that constitutively activating the BMP-receptor Tkv (thick veins) (Tkv-CA) increases the bouton number. The SV proteins Cysteine string protein (CSP) and glutamate vesicular transporter are reduced in Atl-KD and Tkv-CA larvae. Reducing the activity of the BMP receptor Wishful thinking (wit) can rescue both phenotypes. Unlike Tkv-CA larvae, Atl-KD larvae display altered activity-dependent distributions of CSP staining. Furthermore, Atl-KD larvae display an increased FM 1–43 unload than Control and Tkv-CA larvae. As decreasing wit function does not reduce the phenotype, our hypothesis that BMP signaling is not involved is supported. We also found that Rab11/CSP colocalization increased in Atl-KD larvae, which supports the concept that late recycling endosomes regulate SV movements. Conclusions Our findings reveal that Atl modulates neurotransmitter release in motor neurons via SV distribution independently of BMP signaling, which could explain the observed SV accumulation and synaptic dysfunction. Our data suggest that Atl is involved in membrane traffic as well as formation and/or recycling of the late endosome.